ARTIFICIAL INTELLIGENCE IN PRIMARY CARE - THREAT OR SUPPORT FOR THE GENERAL PRACTITIONER? - Ewelina Mączka,; Konrad Strużek,; Agnieszka Kwiatkowska,; Wiktor Tracz,; Patrycja Świercz,; Kinga Teper,; Sandra Khiralla-Gawlik,; Aleksandra Anna Strzelecka,; Aleksandra Ewa Basak,; Jarosław Grzegorz Jarosz, (International Journal of Innovative Technologies in Social Science, 2025)
Background: With the rapid development of information technology, artificial intelligence (AI) is finding more and more applications in medicine, including in primary care (PCP). The potential of AI in improving diagnosis, patient monitoring and practice management is presented, and the ethical and legal challenges of its use are highlighted.Aim: The aim of this paper is to analyse the benefits and risks of implementing AI-based solutions in the daily practice of the family physician.Materials and methods: The scientific literature documents a number of examples of successful use of AI in clinical practice, such as medical decision support systems, diagnostic image analysis, health risk prediction tools, patient telemonitoring or automation of administrative tasks. However, despite the high effectiveness of the technology, research points to a number of limitations: the lack of transparency of the algorithms, the risk of potential errors and biases in decision-making, risks to patient privacy and fears of over-automating the treatment process.Results: Maintaining the doctor-patient relationship and ensuring doctors' decision-making autonomy in the context of AI-generated recommendations becomes particularly important.Conclusions: AI can significantly support general practitioners (GPs) in their daily practice, but the implementation of such technologies must be thoughtful and responsible. Ethical aspects, patient trust, data security and legal liability are crucial. It seems reasonable to create uniform standards and guidelines governing the use of AI in PCPs, while developing digital competence among medical staff. Only then will technology become a real support and not a threat to the quality of healthcare.